Pelindungan Rahasia Dagang Dalam Proses Pengadilan Tertutup Dikaitkan Dengan Undang-Undang Nomor 30 Tahun 2000 Tentang Rahasia Dagang - Tanjung, Stephanie Regina; Amirulloh, Muhamad (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
Intellectual Property is a right that arises from the results of thought that produce a product or process that is useful for humans. One form of Intellectual Property is Trade Secret. Trade Secrets are recognized and protected under Law No. 30 of 2000 concerning Trade Secrets. The purpose of this study is to determine the legal certainty of conducting closed hearings against trade secret violations in the UURD and its comparison with regulations of other countries, as well as determining the legal actions that should be taken by the owner of a trade secret in facing court proceedings to protect trade secrets in relation to the UURD and its comparison with other countries. This study uses a normative juridical method with descriptive analytical research specifications. The comparison method used is the method of comparison of legal instruments, especially comparison of legislation. Data collection techniques used in this study were literature studies and interviews. Based on the research conducted, it can be concluded that the provisions in Article 18 of the Trade Secret Law do not provide legal certainty regarding how trade secrets can be protected in the trial process. The condition in which both parties must request to close the trial is not in line with the Judge's obligation to protect Trade Secrets. The legal remedy that can be taken by the Trade Secret Owner is to request that the trial of the Trade Secret case be held behind closed doors. This application is made not because of the conditions contained in Article 18 UURD, but based on the obligation of the Trade Secret Owner to make all proper efforts to safeguard the Trade Secret. An application to close the trial should not be rejected by the Judge, because refusal is a violation of the Owner's right to maintain a Trade Secret.